Une lecture de politiques urbaines genrées dans des pays émergents - Claire Hancock (EchoGéo)
This paper critically assesses gendered urban policies implemented in large cities in emerging countries, with particular reference to policies facilitating the female public's access to public transportation in Mexico City and Seoul. After discussing the adequate feminist standpoint one can adopt, I review the case studies in order to illuminate some of the social and political tensions in emerging urban societies.